PERANCANGAN DETAIL ENGINEERING DESIGN (DED) LABORATORIUM PLTS BERBASIS TEACHING FACTORY - Patras, Berbie Yesa; Rongkonusa, Dibrian Ananta; Wenno, Leony Ariesta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia sits on the equator and receives some of the most abundant solar irradiation in the world, making Solar Power Plant (SPP) technology a natural fit for the country’s long-term energy strategy. Despite this geographic advantage, one persistent challenge remains: the shortage of technically skilled workers who can install, operate, and maintain SPP systems to industry standards. Vocational education institutions are expected to fill that gap, yet many still operate with laboratory facilities that are outdated, incomplete, and far removed from real working conditions. This study was conducted to address that issue by producing a Detail Engineering Design (DED) for a Teaching Factory-based SPP Laboratory at Politeknik Negeri Manado. The work was carried out using a descriptive engineering design approach, combining literature review, field observation at the campus Renewable Energy Laboratory, and regular supervisory consultations. The design covers load requirement analysis, component sizing for solar modules, Solar Charge Controller, lithium battery and hybrid inverter, electrical installation layout, protection system, Single-Line Diagram, and wiring diagram. The final product is a complete DED package comprising detailed engineering drawings, component specifications, Bill of Quantity, and construction cost estimates. A hybrid system configuration was chosen to ensure a stable power supply throughout laboratory sessions, using solar energy as the primary source with automatic switchover to battery storage or the PLN grid as backup.